Immigration and Competitiveness – Some Methodological Questions - Tünde Patay (DETUROPE)
Immigrants can contribute significantly to the economic and social development of regions or urban areas. Some key figures on migration are thus traditionally used in studies on local development. Beyond the usual description of migratory movements, two research fields are often in the centre of controversies, namely the labour market and the inclusion of immigrants. Comparing the European regions, the phases of urban development as well as the relevant internal and external factors present a mixed picture in Europe. At the same time, the dynamics of migratory movements and the reactions of national and subnational policies also vary. The Member States of the European Union aim to harmonise their definitions and data on migration issues, however, the daily practice leads us to the questions of reliability and comparability of migration statistics; and the interdisciplinary character of migration research offers the use of variable research methods. The aim of this study, as a part of a presentation at a conference on urban development, is to describe some key methodological issues of migration research exploring the typical questions. The first part of the paper calls attention to the importance of data quality, processing and interpretation, describing the research methods mainly used in studies on immigration. The second part summarizes the significance of immigration in regional competitiveness, pointing out the possible “stumbling stones” in the relevant migration studies. Some of these factors, the areas that are mainly in the centre of scientific and political debates, are discussed in this paper, namely the labour market challenges and issues relating to the different aspects of segregation.